SAT0052 High chance of comprehensive disease control (CDC) in very early and normal weight rheumatoid arthritis patients treated according to the treat to target strategy. (15th June 2017) - Fedele, AL; Petricca, L; Tolusso, B; Alivernini, S; Mario, C Di; Sante, G Di; Ferraccioli, G; Gremese, E
Abstract : Background: The ultimate goal for Rheumatoid Arthritis (RA) management is the simultaneous achievement of all clinical, functional and structural efficacy, i.e. comprehensive disease control (CDC) [1]. Objectives: To evaluate the effective chance and the consequences of CDC achievement in real world practice of Early Arthritis Clinic (EAC). Methods: A total of 349 early rheumatoid arthritis (ERA) patients with a disease duration of less than 12 months were enrolled in the study. ERA patients fulfilled the 2010 ACR criteria for RA and were followed according to the treat-to-target strategy. Subjects with symptom duration less than 3 months were defined as having "very early RA" (VERA). The mean follow-up (FU) was 38.2±32.8 months. At baseline, and every three months, the ACR/EULAR core data set variables were recorded. At baseline and every year hand and foot radiographs were examined according to modified Total Sharp score (mTSS). At each visit, clinical improvement and remission were evaluated according to EULAR criteria. The achievement of CDC (28-joint Disease Activity Score using C reactive protein <2.6, Health Assessment Questionnaire <0.5 and change from baseline in mTSS ≤0.5) was assessed every year of follow-up. Results: At the twelfth month of FU 148 (42.4%) ERA patients achieved CDC, while at the time of last FU 228 (65.3%) subjects reached this target. Patients achieving CDC at the 12th month of FU were younger ( p=0.05 ), in higher percentage male ( p=0.004 ), and with a normal weight (body mass index, BMI <25) ( p=0.003 ) and had a shorter disease duration, comprising a greater number of VERA ( p=0.01 ), compared to subjects not achieving disease control. There were no differences concerning autoantibody positivity and presence of erosions at onset between the two analyzed cohorts. Adjusting the analysis for age, the variables that arose as independent predictors of CDC at the 12th month of FU were a disease duration less than 3 months [OR (95% CI): 1.97 (1.23–3.14)] and a normal BMI [OR (95% CI): 2.05 (1.32–3.21)]. In our cohort, 105 (30.1%) ERA patients were treated with biological disease modifying anti-rheumatic drugs (bDMARDs) over time. Biotechnological therapy was less frequently started by subjects in CDC, both after 12 months ( p=0.003 ) and at the time of last FU ( p < 0.0001 ). At the multivariate analysis, not achieving CDC at the 12th month of FU [OR (95% CI): 2.69 (1.59–4.57)] and a BMI ≥25 [OR (95% CI): 2.05 (1.23–3.42)] were the variables significantly associated to bDMARD therapy over time. Conclusions: The simultaneous achievement of symptom control, inhibition of radiographic progression and normalization of function, is a feasible target in real word EAC. Having a VERA and a normal weight are associated to a high chance of "deep" remission. References: Emery P, et al. Ann Rheum Dis 2015; 74: 2165–2174. Disclosure of Interest: None declared